SALES OF JAPANESE SIM CARDS AT PT. ADVENTURE TRAVEL GROUP - Anna Yuliani Pratiwi (Universitas WIdyatama, 2020)
As times progressed, communication and information became rapidly evolving. One of the media used is a mobile phone. Nowadays, especially on vacation abroad, we can't get off the phone. Therefore, a SIM card is created for overseas. At this time, a large number of people who need internet facilities abroad. One of the travel agents opened a special brand SIM Card, to meet the needs of its customers. This makes traveling more practical. In this Final Task report, the author discusses